(untitled) (Samsad Journal संसद जर्नल, 2025)
Riverbed farming (RbF) has emerged as an alternative form of agriculture. This farming supports the poor and marginalized farmers’ adaptation to climate change, especially in degraded lands because of floods and flood-induced riverbank erosions every year. The government and non-government organizations (GOs/NGOs) have supported and built capacities of farmers to adopt this as an effective adaptation strategy in the region. This study aims to analyze the determinants of riverbed farming at the household level mainly in the Deukhuri valley of the Western Terai, Nepal. A total of 150 households were selected randomly for the study in Sisahaniya rural municipality for the household survey. The determinants of the adoption of riverbed farming have been analyzed utilizing independent variables such as age, gender, education, occupation, ethnicity, family size, and others. Education and occupation are positively significant for the adoption of riverbed farming whereas the family size is negatively significant. Agriculture is the main occupation in the area. Education has helped them to understand the concept and procedures of RbF as alternative farming in degraded lands. However, not all the family members have actively contributed to the RbF. This is an interesting study that could be expanded with the support of GOs/NGOs.